2015 Relaunch as Open Access Pediatric Neurology Briefs - John J Millichap; J Gordon Millichap (Pediatric Neurology Briefs, 2015)
Pediatric Neurology Briefs (PNB) has been published monthly since 1987 as a continuing education service designed to expedite and facilitate review of current medical literature concerning pediatric neurology. In 2015, PNB is relaunched as an open access, peer-reviewed, journal with an expanded editorial board.  PNB has a new website and content management system capable of organizing peer-review and providing improved indexing, DOI assignment, and online full-text article view.  Digitization of back issues, archiving, and inclusion in PubMed are future goals.  The new online open access PNB aims to reach more physicians, researchers, and other healthcare providers with highlights of the latest advances in pediatric neurology and commentaries by specialists in the field.